The Effects of Controlled Environment and Diets on Broodstock Maturation, Spawning, Spermatophore Quality and Juvenile Production of Penaeus Merguiensis (De Man) - Olubunmi, Akinfolajimi (1999)
Some aspects of the maturation and artificial propagation of Penaeus merguiensis were studied The percentage of naturally matured shrimps that were transported to the hatchery and spawned was 83 33% while the percentage of hatchery matured shrimps that spawned were 66 66%, 50 00%, 50 00% and 33 33% for broodstocks fed With squids (Loligo sp ), polychaete (Diopatra sp ), Artemza biomass and pellets diets, respectively [he lipid and fatty acid composition of some locally available maturation diets were also determined and compared Analytical results Indicate that the total lipid content (wet weight) of the diets was highest in Lolzgo sp ( 4.30%) followed by that of DlOpalrl1 sp. and enriched adult Artemza at 1.82 % and 1.15 % respectively. The lipid content of pellets was 6.0% (dry weight). Total fatty acid composition of the diets was highest for Lolzgo sp. (7519.74 J.lglg) wet tissue, followed by the total fatty acid contents of Diopatra sp., enriched Artel1lla sp. and pellets at 5554.05 J.lg/g, 1 075.38 J.lg/g and 636.62 J.lg/g wet tissue respectively. Maturation diets have been reported to have certain polyunsaturated fatty acids, which can help trigger maturation. The total polyunsaturated fatty acid contents for Lo/tgo sp., Diopatra sp., enriched adult Artel1ua and pellets were 5899.33 J.lg/g, ] 726.81 J..lg/g, 326.14 J..lg/g and 12.57 J.lg/g constituting 78.46%, 3] .09%,30.33% and 1.98% of the total fatty acid composition respectively. A study was carried out to evaluate the effects of different rearing conditions on the growth and survival of juvenile Penaeus merguiensis in circular and rectangular tanks. Postlarvae P. mergumesls with initial weight of 5.0 mg were reared under varied rearing conditions by utilising trash-fish and commercial pellets, trash-fish and commercial Spirulina, and trash-fish and Skeletonema as treatment A, B, and C respectively. The specific growth rates of the different treatments were 14.53, 10.89 and 12 .] 6 while; the survival rates were 96.92%, 44.39% and 89.55% respectively. There was no significant difference (p< 0.05) in the specific growth rate and survival rate for juveniles fed trash-fish and commercial pellets and the juveniles fed trash-fish and Skeletonema. The specific growth rate and survival rate of juveniles fed trash-fish and Spirulina were found to be significantly lower than in the other two treatments. In another experiment, postlarvae P. merguiensis with an initial weight of about 3.5 mgl postlarva (PL) were reared under two different densities, 1200 and 2400 respectively. All the tanks were fed wit h trash-fish and commercial pellets. T he specific growth rates were 15.34 and 11. 82 while the survival rates were 84.50% and 90.5 7% respectively. However, there was no significant difference (p<0.05) between the values obtained A companion of the performance of circular and rectangular tanks i n terms o f growth and survival o f juveniles stocked at a density o f 1200 per liter shows that juveniles reared in circular tanks had lower specific growth rate than those reared in rectangular tanks. There was a higher survival rate than for juveniles reared i n rectangular tanks. However, these differences are not statistically significant (p <0.05). A more uniform growth was observed for juveniles reared i n raceways (c. V = 32 . 84%) than juveniles reared i n circular tanks (c . V = 34.31 %).